Pembentukan Kompetensi Menulis Hanzi Siswa SMAN 2 Sidoarjo Melalui Mentoring Learning Model dengan Menggunakan Penulisan Kaligrafi sebagai Media - Galih Wibisono; Subandi Subandi; Mamik Tri Wedawati; Muhammad Farhan Masrur; Urip Zaenal Fanani (Universitas Negeri Surabaya, 2023)
The skill of writing letters is a basic competency that is used as a reference for more complex learning process. Learning in Mandarin has no exception, which has a Hanzi typeface which has very basic differences for Indonesian native-speaking learners. To help overcome difficulties writing hanzi , research has been carried out using the mentoring learning model. Through this learning model, students are given the opportunity to be creative and renew their maximum potential to actualize it into works of calligraphy in the form of Chinese writing. During the calligraphy writing process students receive assistance. To get feedback, data analysis was carried out including data obtained from technical observations, aspects of interaction between educators and students, interactions between students, the implementation stage, then data in the form of students' calligraphy writing results, as well as the evaluation stage. Hanzi calligraphy is analyzed based on the number of strokes, stroke order, stroke construction, and aesthetic aspects. Based on the data analysis results can be used to draw conclusions, that the mentoring learning model has shown a very significant role in helping students overcome difficulties and at the same time being able to build competence in writing Chinese hanzi calligraphy.